New Zealand National Gambling Study: 2018 Participant Re-contact and Implications for a 2019 Interview Wave - Bellringer, M; Garrett, N; Abbott, M (Auckland University of Technology, 2018)
Introduction The National Gambling Study (NGS) is a nationally representative longitudinal survey of adults aged 18 years and older, designed to provide information on the prevalence, incidence, nature and effects of gambling in New Zealand. Participants (N=6,251) were recruited in 2012 via face-to-face household recruitment and computer-assisted personal interviews (CAPI). It was designed as a multi-stage, stratified, probability-proportional-to-size sample with oversampling of Māori, Pacific people and Asian people, so that statistical analyses could be conducted on sub-samples by ethnicity. In 2013, one year after initial recruitment and interviewing, 3,745 participants were re-interviewed. The reduced sample was partly due to insufficient budget to attempt re-contact of all participants (only attempted re-contact with 5,266 participants) and partly due to attrition. Numbers re-interviewed in 2014 and 2015 were 3,115 and 2,770, respectively. As the number of moderate-risk and problem gamblers in the NGS is relatively small (about two percent of participants), an additional cohort of 106 adult moderate-risk and problem gamblers was recruited from gambling venues and via advertisements in 2014/15, and reinterviewed in 2015/16. An analysis of data from this additional cohort concluded that: “… it is feasible to combine the MR/PG cohort with the NGS moderate-risk/problem gamblers in order to conduct sub-group analyses, as the two cohorts are similar in the majority of respects. However, as there are some differences between the cohorts, dependent on the analyses being undertaken, weightings may have to be applied to the MR/PG cohort to make it more representative of the general population moderate-risk and problem gamblers.” (Bellringer, Prah, Garrett & Abbott, 2018, p. 7) The NGS was conducted by the Gambling and Addictions Research Centre at Auckland University of Technology (AUT) in collaboration with the National Research Bureau (NRB), an independent research company. In all years, NRB recruited the participants (apart from the additional cohort in 2014/15) and conducted all face-to-face interviews.